The hsp40 Gene Family in Japanese Flounder: Identification, Phylogenetic Relationships, Molecular Evolution Analysis, and Expression Patterns - Yan, Weijie; Qiao, Yingjie; Qu, Jiangbo; Liu, Xiumei; Zhang, Quanqi; Wang, Xubo (Frontiers in Marine Science, 2021)
Heat shock proteins (Hsps) are cellular chaperones that are involved in developmental stages and stress responses. Hsp40 is the major subfamily of heat shock proteins, but has not been fully characterized in Japanese flounder (Paralichthys olivaceus), especially their roles in immune response. In this study, a comprehensive identification and analysis of hsp40 in flounder is presented, including gene structures, evolutionary relationships, conserved domains, molecular evolution analysis, and expression patterns. Sequence features and phylogenetic analysis revealed that hsp40 genes could be grouped into 40 distinct subfamilies and most of them (96%) in Japanese flounder possessed no less than two introns. Molecular evolution analysis indicated that the hsp40 genes were conservative during evolution and were functional-constrained. Meanwhile, hsp40 genes were found to express in different embryonic and larval stages and might play a role of sentinel in healthy organisms. Furthermore, hsp40 genes’ expression profiles after Edwardsiella tarda injection were determined in Japanese flounder without precedent, and 88% (44/50) hsp40 genes showed differential expression patterns after bacterial challenge. Our findings provide basic and useful resources for understanding the immune responsibilities of hsp40 genes in flatfish.